Routine laboratory parameters predict intensive care unit admission and hospitalization in patients suffering stab injuries - Maleitzke, Tazio; Zhou, Sijia; Zocholl, Dario; Fleckenstein, Florian Nima; Back, David Alexander; Plewe, Julius Maximilian; Weber, Jérôme; Winkler, Tobias; Stöckle, Ulrich; Tsitsilonis, Serafeim; Märdian, Sven (Frontiers in Immunology, 2023)
Background: Knife crime increased considerably in recent years in Northern Europe. Affected patients often require immediate surgical care due to traumatic organ injury. Yet, little is known about clinically relevant laboratory parameters in stab injury patients and how these are associated with clinical outcomes. Methods: We retrospectively analyzed 258 stab injury cases between July 2015 and December 2021 at an urban Level-I Trauma Center. Annual and seasonal incidences, injury site, injury mechanism, Injury Severity Score (ISS), and surgical management were evaluated. First, correlations between routine laboratory parameters for hematology, coagulation, and serum biochemistry (peak, and Δ (change from admission to peak within 3 days following admission)) and length of hospital stay, intensive care unit (ICU) stay, and number of surgeries were assessed using Spearman’s rank correlation coefficients. Second, multivariable least absolute shrinkage and selection operator (LASSO) regression analyses identified parameters predictive of clinical outcomes. Third, longitudinal developments of routine laboratory parameters were assessed during hospital admission. Results: In 2021, significantly more stab injuries were recorded compared to previous years and less occurred during winter compared to other seasons. The mean ISS was 8.3±7.3 which positively correlated with length of hospital and ICU stay (r=0.5–0.8, p<0.001). Aspartate transaminase (AST) (Δ) (r=0.690), peak C-reactive protein (CrP) (r=0.573), and erythrocyte count (Δ) (r=0.526) showed the strongest positive correlations for length of ICU stay for penetrating, thoracoabdominal, and organ injuries, respectively. No correlations were observed between routine laboratory parameters and number of surgeries. For patients with penetrating injuries, LASSO-selected predictors of ICU admission included ISS, pH and lactate at admission, and ∆ values for activated partial thromboplastin time (aPTT), K+, and erythrocyte count. CrP levels on day 3 were significantly higher in patients with penetrating (p=0.005), thoracoabdominal (p=0.041), and organ injuries (p<0.001) compared to those without. Conclusion: Our data demonstrate an increase in stab injury cases in 2021 and an important link between changes in routine laboratory parameters and ICU admission and hospitalization. Monitoring ISS and changes in AST, CrP, erythrocyte count, pH, lactate, aPTT, and K+ may be useful to identify patients at risk and adjust surgical and ICU algorithms early on.